Government Efforts to Protect Habitat for the Florida Panther on Private Lands - Elizabeth F. Pienaar; Melissa M. Kreye (EDIS)
Endangered Florida panthers live and breed on state and federal lands in south Florida, but they are a wide-ranging species, and the habitat available to them on public lands is not enough for them to thrive and recover. The 2008 Panther Recovery Plan by the US Fish and Wildlife Service requires that habitat for the panther be conserved on both public and private lands throughout the state. Private rangelands in southwest and south central Florida provide important habitat and prey for the Florida panther. These lands also play a key role in conserving other native species like gopher tortoises, bob white quail, turkeys, deer, vultures, scrub jays, cranes, black bears, and bobcats. Unfortunately, these rangelands are under increasing development pressure as the human population in Florida continues to grow. Multiple policy approaches have been put in place by local, state, and federal governments to address habitat loss and secure natural resources in Florida for our panthers. This 5-page fact sheet  provides a brief overview of existing regulatory and voluntary approaches to help conserve the Florida panther on private lands. Written by Elizabeth F. Pienaar and Melissa M. Kreye, and published by the Department of Wildlife Ecology and Conservation, September 2016.